Impact of Money Supply and Inflation on Economic Growth in Nepal - Kunwar, Santosh; Timilsina, Susmita; Nepal, Sunil; Shrestha, Prizma; Shrestha, Abhisek; Gahatraj, Maya (The Lumbini Journal of Business and Economics, 2023)
The relationship between money supply and economic growth has been receiving more attention than any other subject in the field of monetary economics in recent years. Inflation is an increase in prices that can be translated as a decreases in purchasing power overtime. This paper examines the effect of money supply and inflation on economic growth from 1974/75 to 2020/21. The ARDL co-integration approach is used in the study to determine the relationship between the variables for determining if there is long term co-integration among variables where the bound test has been used. The Narrow Money, Broad Money and Consumer Price Indexare the independent variables respectively with GDPas the dependent variable. The whole dynamics of inflation in developing economies are different, so the idea that inflation is always a monetary phenomenon is important to revisit and reevaluate, especially in relation to developing economies. The study shows that CPI is positively related with economic growth. The evidence suggest that CPI has strong impact on economic growth in the developing countries like Nepal.